Determinants of experience & satisfaction in telehealth psychiatry during the COVID-19 pandemic for patients & providers - Morreale, Michael; Cohen, Ilana; Van Wert, Michael; Beccera, Alexis; Miller, Leslie; Narrow, William; Schweizer, Barbara; Straub, Jason; Zandi, Peter; Ruble, Anne (Frontiers in Psychiatry, 2023)
Introduction: The objective of this study was to characterize the experiences and overall satisfaction of patients and providers with the March 2020 transition to telehealth in a psychiatric setting (telepsychiatry). The study also investigated how socio-demographic and clinical characteristics impact an individual’s experiences and satisfaction with telepsychiatry. Methods: Responses were collected from 604 patients and 154 providers engaged in clinical care at one of three participating Johns Hopkins Medicine outpatient psychiatric clinics between January 2020-March 2021. Survey data were collected by self-report via Qualtrics or telephone follow-up. Results: Respondents were predominately female and White. Over 70% of patients and providers were generally satisfied with telepsychiatry. However, providers were more likely to favor in-person care over telepsychiatry for post-pandemic care 48% to 17% respectively, while 35% rated both modalities equivalently. Patients were more evenly divided with 45% preferring telepsychiatry compared to 42% for in-person care, and only 13% rating them equivalently. Among providers, technical difficulties were significantly associated with both less satisfaction and lower preference for telepsychiatry (odds ratio for satisfaction [ORS] = 0.12; odds ratio for preference [ORP] = 0.13). For patients, factors significantly associated with both lower satisfaction and lower preference for telepsychiatry included technical difficulties (ORS= 0.20; ORP=0.41), unstable access to the internet (ORS=0.46; ORP=0.50), worsening depression (ORS=0.38; ORP=0.36), and worsening anxiety (ORS=0.41; ORP=0.40). Factors associated with greater satisfaction and higher preference for telepsychiatry among patients included higher education (ORS=2.13; ORP=1.96) and decrease in technical difficulties over time (ORS=2.86; ORP=2.35). Discussion: Patients and providers were satisfied with telepsychiatry. However, there were greater differences between them in preferences for continuing to use telepsychiatry post-pandemic. These findings highlight factors that influence patient and provider preferences and should be addressed to optimize the use of telepsychiatry in the future.